CTE 2018 - How cloud technologies continues to transform education - Arnold E. Kiv; Vladimir N. Soloviev; Serhiy O. Semerikov (Academy of Cognitive and Natural Sciences, 2019)
This is an introductory text to a collection of papers from the CTE 2018: The 6th Workshop on Cloud Technologies in Education, which was held in Kryvyi Rih, Ukraine, on the December 21, 2018. It consists of short introduction and some observations about the event and its future.